PREVALENCE OF SARCOCYSTIS IN ALPACAS (LAMA PACOS) AND IN SHEEP DOGS OF A LIVESTOCK COMPANY OF THE CENTRAL HIGHLANDS IN PERU - Santiago, Baudilio (2018)
A study was performed to determine the prevalence of Sarcocystis sp. in alpacas and alpacas’ sheep dogs in a livestockcompany from the central highlands in Perú. Skeletal and cardiac muscle were examined to look for micro or macro cystsof Sarcocystis in alpacas slaughtered in the slaughterhouse. Th e macroscopic cysts were detected by direct observationand microscopic cysts by the Trichinoscope method. Fecal samples from 30% of the sheep dogs were examined by theZinc Sulphate Method. High infection levels for micro or macro cysts (75% to 100%) were found in 2, 3 and 4-yearsold alpacas, respectively, and 36% of alpaca sheep dogs were infected with oocysts or sporocysts. We discuss someepidemiological factors which contribute to the dissemination of this parasite.